2020
DOI: 10.1002/agj2.20180
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated increase in stomatal density and vein dimensions during genetic improvement in rice

Abstract: Rice (Oryza sativa L. ssp. indica) has experienced three distinct phases of considerable yield increases: Green Revolution, utilization of heterosis, and the combination of ideotype and inter‐subspecific hybrid breeding. Crop breeding and selection for high yield have increased radiation use efficiency in modern indica rice varieties. However, the underlying leaf morphological and physiological changes have not been established. Field and pot experiments were conducted in 2016 and 2017. We investigated the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
(104 reference statements)
1
6
0
Order By: Relevance
“…Nevertheless, there was nearly no connection between SZ and SD in the present study (Figure 6B). This finding is the same as previous research, where SD and SZ showed no coincident trend during the breeding process of japonica rice varieties [66]. Although increasing g op within species is possible, by decreasing SZ and increasing SD, this trend may only apply to some species due to variations in the natural habit of species [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, there was nearly no connection between SZ and SD in the present study (Figure 6B). This finding is the same as previous research, where SD and SZ showed no coincident trend during the breeding process of japonica rice varieties [66]. Although increasing g op within species is possible, by decreasing SZ and increasing SD, this trend may only apply to some species due to variations in the natural habit of species [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…Correlations between K leaf and VLA existing in cultivated but not wild rice genotypes illustrate the importance of leaf vein traits during rice domestication or genetic improvement. For example, Wu et al ( 2020 ) revealed that an increase in leaf vein dimensions during rice genetic improvement enhanced leaf gas exchange. In addition to leaf vein traits, leaf morphological traits associated with leaf gas exchange, such as stomatal density and stomatal size in rice, have also been improved during crop genetic improvement (Panda et al, 2018 ; Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wu et al ( 2020 ) revealed that an increase in leaf vein dimensions during rice genetic improvement enhanced leaf gas exchange. In addition to leaf vein traits, leaf morphological traits associated with leaf gas exchange, such as stomatal density and stomatal size in rice, have also been improved during crop genetic improvement (Panda et al, 2018 ; Wu et al, 2020 ). There is a need for establishing the underlying morphological and physiological changes for crop improvement.…”
Section: Discussionmentioning
confidence: 99%
“…g s is mainly determined by stomatal size, stomatal density, stomatal distribution, and especially by stomatal aperture [34,35]. Large stomatal pores and stomatal apertures as well as high stomatal density were suggested to be of benefit for improving g s and A in species [36][37][38][39]. As an important determinant for g s , the stomatal aperture is greatly influenced by plant hydraulic status [40,41].…”
Section: Effects Of Stomatal Conductance On Leaf Net Photosynthetic Ratementioning
confidence: 99%